THE USEFUL CONSEQUENCE OF THE TELLEGEN'S THEOREM - Aleksandr Stepanov; Sergey Stepanov (Вестник Северо-Кавказского федерального университета)
In this work we have shown that the quality of differences pseudomodest on the input and output of the passive circuit is a consequence of the Tellegen's theorem for the two modes of the passive chain. We proposed measure which characterizes presence of measurement errors of input and output operating parameters of the circuit, and we indicated by its linear relationship with the error of the identification results of the circuit parameters according to the measurement of regime parameters on the input and output. We given the equations of communication of this measure with an accuracy of identiication of the circuit parameters. The use of this measure and equations of its connection with the identiication error can be useful for solving the tasks of detection of measurement error and of synthesis of the elements' models of electric networks.